Tindak Tutur Pemimpin dalam Rapat Manajemen: Kajian Pragmatik Konsep Gender dalam Perspektif Budaya dan Bahasa - Yovi - Andriani (Sahafa Journal of Islamic Communication, 2021)
IAbstractIn an organization the leader has an important role as an agent of change. This is also reflected in speech acts that have an intersection with culture and the use of language in conveying messages. This study aims to explain the differences in the use of language forms of speech between male and female leaders in official meetings, BKD management meetings in Banjarnegara Regency. The paradigm used is constructivist, with a qualitative approach and case study method. The informants who become the data sources are the echelon IV-II leaders in the BKD Banjarnegara Regency who occupy positions as structural officials, selected based on purposive sampling and criterion based selection. The research data is in the form of lingual units of speech acts used by female and male leaders in management meeting discourse. The technique of collecting data was by recording, listening, taking notes, observing (observation) and interviewing techniques. The analysis refers to pragmatic analysis which emphasizes means-end analysis and heuristics. The results show that culture and language cannot be separated and culture is always attached, integrated in the context of language. All cultures have a set of perceptions, behaviors, and values that are related to many things, one of which is gender roles and authority. The speeches conveyed by female leaders in management meetings tend to be expressive, sympathetic and negative, while the speeches of male leaders tend to be directive. Expressive and sympathetic speech is intended to please others because it does not address the needs of the speaker but rather the needs of the listener. Meanwhile, directive utterances tend to be confrontational and competitive and lead to the needs of speakers rather than listeners. The negative utterances spoken by female leaders tend to be in the form of questions, doubtful whether the choice of words they use is wrong or less acceptable to the listeners by using non-literal, indirect techniques. However, negative utterances at male leaders tend to get to the heart of the problem, in the form of asking something literal, rational and direct.